2012
DOI: 10.1111/febs.12059
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of glycogen synthase from mammalian skeletal muscle – a unifying view of allosteric and covalent regulation

Abstract: It is widely accepted that insufficient insulin-stimulated activation of muscle glycogen synthesis is one of the major components of non-insulindependent (type 2) diabetes mellitus. Glycogen synthase, a key enzyme in muscle glycogen synthesis, is extensively regulated, both allosterically (by glucose-6-phosphate, ATP, and others) and covalently (by phosphorylation). Although glycogen synthase has been a topic of intense study for more than 50 years, its kinetic characterization has been confounded by its large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 135 publications
(285 reference statements)
3
54
2
1
Order By: Relevance
“…In a recent review of the kinetics and regulation of GS [13], we suggested that the available kinetic data of this enzyme are compatible with what is predicted for an MWC (Monod-Wyman-Changeux)-type enzyme in which allosteric and covalent modification alter the apparent equilibrium between the T (taut) and R (relaxed) conformations of the enzyme. The proposed model promises to simplify the kinetic characterization of GS significantly, because the effect of phosphorylation is described by a single parameter.…”
Section: Introductionmentioning
confidence: 55%
See 2 more Smart Citations
“…In a recent review of the kinetics and regulation of GS [13], we suggested that the available kinetic data of this enzyme are compatible with what is predicted for an MWC (Monod-Wyman-Changeux)-type enzyme in which allosteric and covalent modification alter the apparent equilibrium between the T (taut) and R (relaxed) conformations of the enzyme. The proposed model promises to simplify the kinetic characterization of GS significantly, because the effect of phosphorylation is described by a single parameter.…”
Section: Introductionmentioning
confidence: 55%
“…Of the three models we will here limit ourselves to the MWC model. We have previously argued [13] that both the Hill and Koshland-Némethy-Filmer models have features that are either incompatible with GS kinetics or result in equations that are too complex.…”
Section: Gs Rate Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, both starch and glycogen synthases have been discovered that utilize either ADPglucose or UDPglucose (or both; Deschamps et al, 2006) as hexosyl donor. Ample evidence has been presented that these enzymes are essential biosynthetic enzymes (Ballicora et al, 2003;Zeeman et al, 2010;Roach et al, 2012;Palm et al, 2013). Furthermore, it is widely accepted that in glycogenstoring cells, phosphorylase is indispensible for the degradation of the storage polysaccharide (Hwang et al, 1989;Alonso-Casajús et al, 2006;Wilson et al, 2010;Roach et al, 2012;Gazzerro et al, 2013).…”
mentioning
confidence: 99%
“…The activities of ancillary pathways of glucose metabolism are regulated in part through expression of their rate-limiting or committed-step enzymes, cofactor availability, allosterism, and/or post-translational modifications [e.g., [252][253][254][255][256][257][258] ]. Flux through these pathways may be regulated by other means as well.…”
Section: Discussionmentioning
confidence: 99%